The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1159/000369258
|View full text |Cite
|
Sign up to set email alerts
|

23-Gauge versus 25-Gauge Vitrectomy for Proliferative Diabetic Retinopathy: A Comparison of Surgical Outcomes

Abstract: Purpose: This study compared clinical outcomes and complications between 23-gauge (23g) and 25-gauge (25g) transconjunctival sutureless vitrectomy in patients with proliferative diabetic retinopathy. Study Design: It was a retrospective study using data prospectively defined and collected. 80 eyes underwent 23g transconjunctival sutureless vitrectomy, and 80 eyes underwent 25g surgery using the same vitrectomy system by one surgeon. Primary outcome measures were best-corrected visual acuity, intraocular pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 29 publications
1
12
1
Order By: Relevance
“…The incidence of the iatrogenic breaks in our study (4.4%) did not differ significantly from the 5% incidence in a study conducted by Berrocal 16 utilizing 25g all probe lift and shave technique in cases with diabetic TRD. Consistently with these results, Guthrie et al 14 reported insignificant difference in the type or the frequency of iatrogenic breaks in their study comparing 23g and 25g in cases with PDR. Higher incidence (8.3%) for iatrogenic breaks was observed in a study employing 27g pars plana vitrectomy (PPV).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The incidence of the iatrogenic breaks in our study (4.4%) did not differ significantly from the 5% incidence in a study conducted by Berrocal 16 utilizing 25g all probe lift and shave technique in cases with diabetic TRD. Consistently with these results, Guthrie et al 14 reported insignificant difference in the type or the frequency of iatrogenic breaks in their study comparing 23g and 25g in cases with PDR. Higher incidence (8.3%) for iatrogenic breaks was observed in a study employing 27g pars plana vitrectomy (PPV).…”
Section: Discussionsupporting
confidence: 58%
“…Scissors were used in three eyes versus six eyes using 25g and 23g, respectively, in a study conducted by Guthrie et al 14 comparing the two systems. However, the difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Our finding, that the vitrectomy gauge did not correlate with better anatomic success or better visual outcomes, is in accordance with those of other groups. [14][15][16] Our study demonstrates that diabetic ischemia is largely responsible for poor visual outcomes. The question remains whether earlier medical or surgical intervention could offer better hope for these patients.…”
Section: Discussionmentioning
confidence: 61%
“…After core vitrectomy, delamination and removal of all posterior hyaloid face and fibrovascular membranes were carried out. This was done primarily with the vitreous cutter alone, and intravitreal scissors were used only if necessary, as previously described [14,15]. Careful inspection to detect the presence of vitreoschisis was carried out, and staining of residual vitreous gel using diluted triamcinolone (TMC) was used in all cases.…”
Section: Methodsmentioning
confidence: 99%